Penerapan Discovery Learning Berbantuan GeoGebra Untuk Meningkatkan Kemampuan Pemahaman Konsep Persamaan Lingkaran Siswa Kelas XI IPA 3 SMA Negeri 1 Fatuleu - Noman, Marfin Marlisye; Garak, Siprianus Suban; Wangge, Magdalena (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to improve the ability to understand the concept of circle equations by applying the Discovery Learning model assisted by Geogebra. This type of research is classroom action research using the Kurt Lewin model which is carried out in 2 cycles and each cycle consists of 4 stages, namely: (1) planning, (2) implementation, (3) observing, and (4) reflection. The data collection techniques used are tests, observation, and documentation with the data analysis used is quantitative data analysis. The research results showed that the percentage of classical completeness in students conceptual understanding abilities reached 66,67% in cycle I and increased to 83,33% in cycle II. The implementation of the Discovery Learning model assisted by GeoGebra also increases teacher activity and student activity in each cycle with a percentage reaching 100%. Based on the research results, it can be concluded that the application of the Discovery Learning model assisted by GeoGebra can improve the ability to understand the concept of circle equations in class XI IPA 3 Student at SMA Negeri 1 Fatuleu